Selectivity of nicosulfuron and atrazine on different corn hybrids - Barroso, Alberto Leão de Lemos; Dan, Hugo Almeida; Dan, Lilian Gomes de Moraes; Ferreira Filho, Wander Cruvinel; Menezes, Carlos César Evangelista; Melo Filho, Luiz Cobiniano (Comunicata Scientiae, 2012)
Nicosulfuron and atrazine are herbicides widely used for weed control on corn crops. However, itsselectivity is often fairly questionable due to genotypic variability of hybrids in the market. In thiscontext, this study aims to assess both nicosulfuron selectivity and atrazine mixture in 34 corn hybrids.Treatment was arranged in a completely randomized block design, in a split-plot scheme (34x5)with four replicates, in which corn hybrids constituted the plots and herbicides the subplots. 34 cornhybrids were submitted to four herbicide treatments: nicosulfuron (rates of 50 and 60 g ha-1) andnicosulfuron + atrazine (20 + 1500 and 40 + 3000 g ha-1) as well as a non treated check for each hybrid.Application was performed at 19 days (V4/V5) after corn emergence. Phytointoxication symptomswere assessed at 7; 14 and 21 days after treatment application. One thousand grain weight andhybrid yield were also determined. Based on the results, it was observed that the phytotoxic effectsof nicosulfuron+atrazine (40+3000 g ha-1) were enough to reduce the weight of 1000 seeds in hybridsBMX61, BMX750, and NB7405. Nevertheless, herbicide treatments, either alone or associated withatrazine, were selective to the 34 genotypes studied.